Design method, preparation method and application of a RE-Fe-based room temperature magnetic refrigeration material
Design RE-Fe-based room temperature magnetic refrigeration materials through first-principle calculations, introduce Si elements and use rare earth element RE to adjust the phase transition temperature, solve the problem of long heat treatment time in the prior art, and achieve good magnetic refrigeration near room temperature Rapid formation and application of properties of materials.
Patent Information
- Application Number
- CN202111353830.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-16
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-11-16
AI Technical Summary
The heat treatment process of existing RE2Fe17-based room temperature magnetic refrigeration materials takes a long time, resulting in large energy losses and is difficult to meet the needs of rapid application.
The composition of RE-Fe-based room temperature magnetic refrigeration material is designed using first-principle calculation method, and the alloy formation energy is reduced by introducing Si elements, and the phase transition temperature is adjusted using rare earth elements RE and Si, so that the material has good magnetic magnetic around room temperature. Refrigeration performance.
It is realized that the RE-Fe-based room temperature magnetic refrigeration material with good magnetic refrigeration capability is formed in a short time, which reduces the heat treatment time and improves the performance reliability and production efficiency of the material.
Smart Images

Figure CN114067932B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of magnetic refrigeration materials, and in particular relates to a design method, a preparation method and an application of a RE-Fe-based room temperature magnetic refrigeration material. Background Art
[0002] Magnetic refrigeration technology is considered a potential alternative to traditional gas compression refrigeration technology due to its advantages such as high energy efficiency, low environmental pollution and low working noise. The main principle of magnetic refrigeration technology is the magnetocaloric effect, that is, the thermal response of magnetic materials to external magnetic fields. Magnetic refrigeration materials are the most important part in determining the refrigeration effect of magnetic refrigeration machines, so they have become the focus of everyone's research.
[0003] In recent years, a series of magnetic refrigeration materials with second-order phase transition have been considered as potential magnetic refrigeration materials because of their low thermal hysteresis and magnetic hysteresis, wide operating temperature range and good mechanical stability. Such as Gd-based compounds, LaMnO3 series compounds, Fe-based amorphous alloys and RE2Fe 17 Compounds (RE = rare earth). At present, the magnetic refrigeration materials used are mainly rare earth Gd-based materials, but due to the high price of rare earth Gd, finding new room temperature magnetic refrigeration materials is still the goal of everyone's research. Among the above-mentioned second-order phase change materials, RE2Fe 17 The compound has its unique advantages: high magnetization intensity and low cost due to high iron content, and a Curie temperature close to room temperature. 17 The compound has attracted much attention in room-temperature magnetic refrigeration technology.
[0004] Patent CN1598977A discloses a rare earth-iron room temperature magnetic refrigeration material and its preparation method, the chemical formula of which is Pr2Fe 17-x Co x (0≤x<0.1), Th2Zn is obtained by smelting and long-term annealing 17 The 2:17 type compound with a hexagonal structure of type (2:17R). Its cost is lower than that of Gd-based compounds, and its chemical properties are stable. However, the annealing process of this method is time-consuming, requiring annealing for 168 hours at 1173K, with large energy loss and long process cycle. Patent CN110551941A discloses a mixed rare earth-based 2:17 type room temperature magnetic refrigeration material R 2±x Fe 17-y M yAnd its preparation method and application, wherein the mixed rare earth contains 25-35wt.% La, 45-55wt.% Ce, 4-10wt.% Pr and 14-18wt.% Nd, M is one or more of B, C, Al, Si, Ga, Ge, In, Sn, Ti, Pb, and the content y is 0-1.5. This method uses mixed rare earth to reduce the cost of rare earth, but the use of mixed rare earth will cause the performance of the material to be unable to be accurately regulated due to the fluctuation of the composition of the mixed rare earth. Patent CN 111172457A discloses a lanthanum-free mixed rare earth-based room temperature magnetic refrigeration material and its preparation and application, wherein the mixed rare earth contains 60-80wt.% Ce, 5-13wt.% Pr and 18-24wt.% Nd. The annealing process of these methods is still time-consuming, and the temperature is kept at 1220K for 7 days, that is, 168h, and the energy loss is large. Shortening the heat treatment time is of great significance for the application of such materials. Summary of the invention
[0005] In view of the shortcomings of the prior art, the first object of the present invention is to provide a design method for a RE-Fe-based room temperature magnetic refrigeration material. The designed room temperature magnetic refrigeration material has a chemical formula of Ce 2-x RE x Fe 17-y Si y , where RE = Pr, Nd, and 0.1 ≤ x < 0.5, 0.2 < y ≤ 1. The c / a value of the alloy, Fe 6c The distance between atoms of Fe 6c-6c and the alloy formation energy E form , select the one that can increase Fe 6c-6c The value of the alloy composition that reduces the 2:17 phase formation energy is adjusted, the phase transition temperature is adjusted near room temperature (273K-300K), and the required composition selection system of room temperature magnetic refrigeration materials is designed to meet the needs of magnetic refrigeration materials and magnetocaloric ice melting materials at room temperature.
[0006] The second object of the present invention is to provide a method for preparing RE-Fe based room temperature magnetic refrigeration material.
[0007] The third object of the present invention is to provide an application of RE-Fe based room temperature magnetic refrigeration material.
[0008] To achieve the above object, the present invention adopts the following technical solution:
[0009] The present invention provides a design method for a RE-Fe-based room temperature magnetic refrigeration material. The chemical formula of the designed room temperature magnetic refrigeration material is: Ce 2-x RE x Fe 17-y Si y, wherein RE is selected from Pr or Nd, and 0.1≤x<0.5, 0.2<y≤1.
[0010] The inventors studied the effects of adding a large amount of elements on RE2Fe 17 The influence of compound structure and formation energy, it is found that the introduction of Si can best reduce Ce2Fe 17 The formation energy of compound alloys, while the substitution of rare earth elements RE (RE = Pr, Nd) and non-metallic elements Si increases the c / a value and Fe 6c-6c , adjust the phase change temperature of the material near room temperature, so as to obtain magnetic refrigeration materials and magnetic thermal ice-melting materials that meet the requirements at room temperature.
[0011] The preferred solution is that the design method is performed using a first-principles calculation method based on density functional theory, the calculation is performed using a VASP software package, and the projection augmented wave (PAW) method and GGA-PBE exchange correlation potential are used for calculation; the calculation comprises the following steps:
[0012] ① Selection of basic parameters for calculation
[0013] Select lattice constant Ce2Fe 17 The unit cell is used as the initial structure. The unit cell contains 57 atoms, of which Ce occupies the 6c position, and Fe occupies the 6c, 9d, 18f and 18h positions respectively. 2-x RE x Fe 17-y M y The unit cell parameters and atomic occupancy of the ion matrix are completely relaxed, and the convergence criteria for electronic self-consistency and ion relaxation are set to 10 -7 eV and , the cutoff energy is 600 eV, and the K-point grid is 5×5×3; In addition, the “Hubbard U” method is used to treat the 4f orbitals of rare earth atoms, and the U value of Ce is taken as 4 eV;
[0014] Wherein RE is selected from one of Pr, Nd, Sm, La, Dy, Gd,
[0015] M is selected from one of Si, Al, Ga, Ge, Sn, P, Mg, Cr, Ti, and V;
[0016] ② Atoms in Ce2Fe 17 Occupancy calculation in a unit cell.
[0017] Substituting M atoms for Ce2Fe 17 The Fe at the 6c, 9d, 18f and 18h crystal positions in the unit cell are calculated according to the calculation parameters in ① to calculate the Ce2Fe containing M. 17 The formation energy of the unit cell Eform , determine that M atoms are in Ce2Fe 17 Atomic occupancy in a unit cell;
[0018] ③Alloy composition design.
[0019] According to the calculation results of ②, Si atoms are selected to occupy the position, and R atoms are substituted for the 6c crystal position of Ce. According to the calculation parameters in ①, Ce is calculated and obtained. 2-x RE x Fe 17-y M y The cell parameters a and c of the alloy were obtained, and the c / a value and the atomic distance between Fe atoms at the 6c crystal position were obtained to quantitatively determine the influence of alloy composition on the Curie temperature. 2-x RE x Fe 17-y M y The formation energy of the alloy is the lowest when RE is selected from Pr or Nd, M is Si, and 0.1≤x<0.5, 0.2 <y≤1. Therefore, the chemical formula of the magnetic refrigeration material is designed: Ce 2-x RE x Fe 17-y Si y , wherein RE is selected from Pr or Nd, and 0.1≤x<0.5, 0.2<y≤1.
[0020] The present invention also provides a method for preparing a RE-Fe-based room temperature magnetic refrigeration material, comprising the following steps:
[0021] According to the designed proportion, the raw materials Ce source, RE source, Fe source and Si source are weighed, and then the Ce source, RE source, Fe source and Si source are smelted under a protective atmosphere, the uniformly smelted alloy liquid is cast to obtain an alloy ingot, the alloy ingot is heat treated under a protective atmosphere, and cooled to obtain the alloy.
[0022] In the present invention, the Ce source, RE source, Fe source and Si source are selected from pure substances or alloys.
[0023] In a preferred embodiment, when weighing the raw materials, an excess of 5% of rare earth metal is added to compensate for the loss.
[0024] In the present invention, the protective atmosphere used is high-purity argon.
[0025] The preferred solution is to place the raw materials in a crucible of a vacuum rapid solidification melting furnace; evacuate the furnace to a vacuum degree of ≤5×10 -2 Pa; introduce argon gas to make the pressure in the furnace 40-80kPa; send electricity to melt the raw materials, and use electromagnetic force to automatically stir the liquid for refining.
[0026] In a preferred embodiment, the smelting temperature is 1350-1500° C. and the smelting time is 4-10 min.
[0027] In a preferred embodiment, the uniformly smelted alloy liquid is cast onto a rotating water-cooled copper plate to obtain an alloy ingot.
[0028] Preferably, the heat treatment temperature is 1050-1200° C. and the heat treatment time is 2-5 hours.
[0029] In the actual operation process, the alloy ingot is placed in a vacuum heat treatment furnace and evacuated to a vacuum degree better than 10 -2 Pa, and then high-purity argon gas is introduced and heat treatment is carried out under the protection of high-purity argon gas.
[0030] In a preferred embodiment, after the heat treatment is completed, the mixture is quickly quenched in water and cooled to room temperature.
[0031] The present invention also provides an application of a RE-Fe-based room temperature magnetic refrigeration material, and the RE-Fe-Si-based room temperature magnetic refrigeration material is applied to the field of room temperature refrigeration or the field of magnetic thermal ice melting.
[0032] Compared with the prior art, the present invention has the following advantages:
[0033] (1) The present invention innovatively obtains the value of c / a and Fe by first-principles calculation. 6c The distance between atoms and the alloy formation energy E form , the composition of RE-Fe-based room-temperature magnetic refrigeration materials was designed. The material performance is reliable, and a lot of material preparation and component screening time can be saved, which has significant advantages.
[0034] (2) Substitution of rare earth elements RE (RE = Pr, Nd) and non-metallic elements Si increases the c / a value and the distance between Fe atoms at the 6c position The phase transition temperature of the material is adjusted to be near room temperature (273K-300K).
[0035] (3) By adding Si element, the formation energy of 2:17R phase is reduced, so that the phase can be formed in a short time, and the structure can be quickly homogenized. Compared with the heat treatment time of conventional 2:17 type RE-Fe alloy (6-14 days), the heat treatment time of this patent can be reduced to 2-5h.
[0036] (4) Ce of the present invention 2-x RE x Fe 17-y Si y The refrigeration material has good magnetic refrigeration capability and can be used in the fields of room temperature refrigeration and magnetic thermal ice melting. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The Ce prepared in Comparative Example 3 of the present invention 1.6 Nd 0.4 Fe 17 XRD diagram of the main phase of Th2Zn 17 2:17R phase with type structure.
[0038] Figure 2 The Ce prepared in Comparative Example 3 of the present invention 1.6 Nd 0.4 Fe 17 SEM image of the 2:17R phase. The gray phase is the 2:17R phase and the black phase is the α-Fe phase, which proves that the α-Fe phase has a high content.
[0039] Figure 3 Ce2Fe 16.7 Si 0.33 and Ce2Fe 17 The local state density of atoms in the alloy is Figure 3 (a) is the local density of states of Si atoms and Figure 3 (b) Local density of states of Fe atoms and their nearest neighbors; Figure 3 (c) Ce2Fe 17 The local state density of Fe atoms in Ce2Fe 16.7 Si 0.33 Two new states appear at -8.9 eV and -6 eV, which are composed of the 2s orbital of Si, the 3s orbital of Fe, and the 3p orbital of Fe, indicating that electronic hybridization occurs between Fe and Si. This hybridization reduces the formation energy of Ce-Fe alloy.
[0040] Figure 4 The Ce prepared in Example 1 of the present invention 1.6 Nd 0.4 Fe 16.7 Si 0.33 XRD diagram of the main phase of Th2Zn 17 2:17R phase with type structure.
[0041] Figure 5 The Ce prepared in Example 1 of the present invention 1.6 Nd 0.4 Fe 16.7 Si 0.33 SEM image of the alloy. The gray phase is the 2:17R phase and the black phase is the α-Fe phase, which indicates that the α-Fe phase has a high content. DETAILED DESCRIPTION
[0042] Comparative Example 1Ce2Fe 17 Preparation
[0043] (1) Raw material preparation: According to the chemical formula Ce2Fe 17 , weigh the raw materials Ce and Fe, among which the rare earth metal is added in excess of 5% to make up for the loss.
[0044] (2) Alloy smelting: Alloy ingots are smelted using vacuum induction melting technology. The weighed raw materials are placed in the crucible of a vacuum rapid solidification smelting furnace; vacuum is drawn to a vacuum degree of 7×10 -3 Pa; high-purity argon gas is introduced to make the pressure in the furnace 60kPa; electricity is supplied to melt the raw materials, and the liquid is automatically stirred by electromagnetic force for refining. The temperature of the alloy liquid is 1400℃ and kept warm for 8 minutes; then, the uniformly smelted alloy liquid is cast onto a rotating water-cooled copper plate to obtain an ingot with uniform composition.
[0045] (3) Place the alloy ingot in a vacuum heat treatment furnace and evacuate to 6×10 -3 Pa, and then high-purity argon gas was introduced and kept at 1100℃ for 3h. After the insulation, it was quickly quenched in water and cooled to room temperature.
[0046] The block was broken and measured, and X-ray diffraction proved that the main phase was Th2Zn 17 The SEM image shows that there are a lot of black α-Fe phases. The phase transition temperature measured by the comprehensive physical property measurement system (PPMS) is 225K. The Curie temperature is much lower than room temperature and cannot meet the use requirements of the material near room temperature.
[0047] Comparative Example 2Ce2Fe 17 Preparation
[0048] (1) Raw material preparation: same as that of Comparative Example 1.
[0049] (2) Alloy smelting: same as Comparative Example 1.
[0050] (3) Place the alloy ingot in a vacuum heat treatment furnace and evacuate to 6×10 -3 Pa, and then high-purity argon gas was introduced and kept at 1100℃ for 60h. After the insulation, it was quickly quenched in water and cooled to room temperature.
[0051] The block was broken and measured, and X-ray diffraction proved that the main phase was Th2Zn 17 The SEM image shows that there are many black α-Fe phases.
[0052] Comparative Example 3Ce 1.6 Nd 0.4 Fe 17 Preparation
[0053] (1) Raw material preparation: according to the chemical formula Ce 1.6 Nd 0.4 Fe 17 , weigh the raw materials Ce, Nd, and Fe, among which the rare earth metal is added in excess of 5% to make up for the loss.
[0054] (2) Alloy smelting: Alloy ingots are smelted using vacuum induction melting technology. The weighed raw materials are placed in the crucible of a vacuum rapid solidification smelting furnace; vacuum is drawn to a vacuum degree of 7×10 -3 Pa; high-purity argon gas is introduced to make the pressure in the furnace 60kPa; electricity is supplied to melt the raw materials, and the liquid is automatically stirred by electromagnetic force for refining. The temperature of the alloy liquid is 1400℃ and kept warm for 8 minutes; then, the uniformly smelted alloy liquid is cast onto a rotating water-cooled copper plate to obtain an ingot with uniform composition.
[0055] (3) Place the alloy ingot in a vacuum heat treatment furnace and evacuate to 6×10 -3 Pa, and then high-purity argon gas was introduced and kept at 1100℃ for 3h. After the insulation, it was quickly quenched in water and cooled to room temperature.
[0056] The block was broken and measured, and X-ray diffraction proved that the main phase was Th2Zn 17 2:17R phase of type structure (such as Figure 1 shown). Figure 2 The SEM image is shown, in which the gray is the 2:17R phase and the black is the α-Fe phase, with a higher content of α-Fe. The phase transition temperature measured by PPMS is 273K, and under an external field of 5T, |ΔS M |The maximum value is about 4.1 J / kg K, and appears near 273 K. Under an external field of 5 T, the operating temperature range can reach 95.5 K, and the refrigeration capacity (RCP) reaches 371 J / kg.
[0057] Comparative Example 4Ce 1.6 Nd 0.4 Fe 17 Preparation
[0058] (1) Raw material preparation: same as Comparative Example 3.
[0059] (2) Alloy smelting: Same as Comparative Example 3.
[0060] (3) Place the alloy ingot in a vacuum heat treatment furnace and evacuate to 6×10 -3 Pa, and then high-purity argon gas was introduced and kept at 1100℃ for 60h. After the insulation, it was quickly quenched in water and cooled to room temperature.
[0061] The block was broken and measured, and X-ray diffraction proved that the main phase was Th2Zn 17The SEM image shows that there are more α-Fe phases.
[0062] Comparative Example 4Ce 1.6 Nd 0.4 Fe 16.67 Al 0.33 Ingredient design
[0063] The first-principles calculations based on density functional theory were performed using the VASP software package, using the projector augmented wave (PAW) method and the GGA-PBE exchange-correlation potential for approximate calculations.
[0064] ① Selection of basic parameters for calculation
[0065] Select lattice constant Ce2Fe 17 The unit cell is used as the initial structure. The unit cell contains 57 atoms, of which Ce occupies the 6c position and Fe occupies the 6c, 9d, 18f and 18h positions respectively. The unit cell parameters and atomic occupancy are fully relaxed. The convergence criteria for electronic self-consistency and ion relaxation are set to 10-7eV and , the cutoff energy is 600 eV, and the K-point grid is 5 × 5 × 3. In addition, the “Hubbard U” method is used to treat the 4f orbitals of rare earth Ce atoms to obtain accurate results, and the U value of Ce is taken as 4 eV.
[0066] ②Al atoms in Ce 1.6 Nd 0.4 Fe 16.67 Al 0.33 Occupancy calculation in a unit cell.
[0067] Substitute one Al atom for Fe at the 6c, 9d, 18f, and 18h crystal positions, and calculate Ce 1.6 Nd 0.4 Fe 16.67 Al 0.33 Formation energy. According to the calculation results, when Al replaces Fe, the formation energy (E form ) is the lowest, which is -0.154 eV / fu, indicating that Al preferentially occupies the 18h crystal site of Fe.
[0068] Comparative Example 5Ce 1.6 Nd 0.4 Fe 16.67 Ga 0.33 Ingredient design
[0069] The first-principles calculations based on density functional theory were performed using the VASP software package, using the projector augmented wave (PAW) method and the GGA-PBE exchange-correlation potential for approximate calculations.
[0070] ① Selection of basic parameters for calculation
[0071] The selection of basic parameters is the same as that of Comparative Example 4.
[0072] ②Ga atoms in Ce 1.6 Nd 0.4 Fe 16.67 Ga 0.33 Occupancy calculation in a unit cell.
[0073] Substitute one Ga atom for Fe at the 6c, 9d, 18f, and 18h crystal positions, and calculate Ce 1.6 Nd 0.4 Fe 16.67 Ga 0.33 Formation energy. According to the calculation results, when Ga replaces Fe, the formation energy (E form ) is the lowest, which is -0.194 eV / fu, indicating that Ga preferentially occupies the 18h crystal site of Fe.
[0074] Example 1Ce 1.6 Nd 0.4 Fe 16.67 Si 0.33 Composition design and preparation
[0075] (1) Alloy composition design
[0076] The first-principles calculations based on density functional theory were performed using the VASP software package, using the projector augmented wave (PAW) method and the GGA-PBE exchange-correlation potential for approximate calculations.
[0077] ① Selection of basic parameters for calculation
[0078] Select lattice constant Ce2Fe 17 The unit cell is used as the initial structure. The unit cell contains 57 atoms, of which Ce occupies the 6c position and Fe occupies the 6c, 9d, 18f and 18h positions respectively. 2-x RE x Fe 17-y Si y The unit cell parameters and atomic occupancy of the ion relaxation are completely relaxed. The convergence criteria for electronic self-consistency and ion relaxation are set to 10 -7 eV and , the cutoff energy is 600 eV, and the K-point grid is 5 × 5 × 3. In addition, the “Hubbard U” method is used to treat the 4f orbital of the rare earth Ce atom to obtain accurate results, and the U value of Ce is taken as 4 eV.
[0079] ②Si atoms in Ce2Fe 17 Occupancy calculation in a unit cell.
[0080] Substituting one Si atom for Fe in the 6c, 9d, 18f, and 18h crystal positions, calculate Ce2Fe 17 Si formation energy. According to the calculation results, when Si replaces Fe, the formation energy (E form ) are -0.011, -0.402, -0.403 and -0.454 eV / fu, respectively, indicating that Si preferentially occupies the 18h crystal position of Fe, and its formation energy is much lower than that of comparative examples 4 and 5 after substitution with Al and Ga. Therefore, Si is selected as the added element.
[0081] ③Alloy composition design.
[0082] Select four alloy compositions Ce2Fe 17 、Ce2Fe 16.7 Si 0.33 、Ce 1.67 Nd 0.33 Fe 17 、Ce 1.67 Nd 0.33 Fe 16.7 Si 0.33 , where Si occupies the 18h crystal position of Fe and Nd occupies the 6c crystal position of Ce. Calculate the structural parameters of the alloy, the distance d between Fe atoms on the 6c crystal position Fe6c-6c and formation energy E form The results are shown in Table 1. Figure 3 As shown in Table 1, the substitution of rare earth element Nd and non-metallic element Si increases the c / a value and the distance d between Fe atoms at the 6c position. Fe6c-6c , which is beneficial to the increase of Curie temperature. Figure 5 It can be seen that after the addition of Si element, Ce2Fe 16.7 Si 0.33 It can be found in the local state density diagram that two new states appear at -8.9eV and -6eV. The state is composed of Si 2s orbital, Fe 3s orbital and Fe 3p orbital, indicating that electronic hybridization occurs between Fe and Si. This hybridization reduces the formation energy of Ce-Fe alloy, where: Ce2Fe 16.7 Si 0.33 is -0.454eV / fu, which is lower than Ce2Fe 17-0.056eV / fu is about 0.4eV / fu lower; Ce 1.67 Nd 0.33 Fe 16.7 Si 0.33 Comparison 1.67 Nd 0.33 Fe 17 The formation energy of the alloy is reduced, which is conducive to the formation of the alloy after a short heat treatment and the rapid homogenization of the organizational structure. Compared with Comparative Examples 4 and 5, it can be found that the formation energy of adding Al and Ga is only reduced by 0.098 and 0.138 eV / fu, which is much lower than the addition of Si element. In the composition design, this patent selects to add different contents of Nd and Si to increase the Curie temperature of the material.
[0083] (2) Raw material preparation: According to the chemical formula Ce 1.6 Nd 0.4 Fe 16.67 Si 0.33 , weigh the raw materials Ce, RE, Fe, Si, among which the rare earth metal is added in excess of 5% to make up for the loss.
[0084] (3) Alloy smelting: Alloy ingots are smelted using vacuum induction melting technology. The weighed raw materials are placed in the crucible of a vacuum rapid solidification smelting furnace; vacuum is drawn to a vacuum degree of 7×10 -3 Pa; high-purity argon gas is introduced to make the pressure in the furnace 60kPa; electricity is supplied to melt the raw materials, and the liquid is automatically stirred by electromagnetic force for refining. The temperature of the alloy liquid is 1400℃ and kept warm for 8 minutes; then, the uniformly smelted alloy liquid is cast onto a rotating water-cooled copper plate to obtain an ingot with uniform composition.
[0085] (4) Alloy homogenization heat treatment: Place the above alloy ingot in a vacuum heat treatment furnace and evacuate to a vacuum degree better than 10 -2 Pa, and then high-purity argon gas was introduced and kept at 1100℃ for 3h. After the insulation, it was quickly quenched in water and cooled to room temperature.
[0086] The block was broken and measured, and X-ray diffraction proved that the main phase was Th2Zn 172:17R phase with type structure. Its SEM image is shown, in which the gray is the 2:17R phase and the black is the α-Fe phase, and the α-Fe phase content is significantly less than that in Example 2. It shows that the addition of Si element reduces the formation energy of the 2:17R phase and promotes the formation of this phase. The phase transition temperature was measured to be 297K by the comprehensive physical property measurement system (PPMS), as well as the isothermal magnetization curve near the phase transition temperature, with a measurement step of 4K. The slope of the Arrott curve in the illustration is positive, indicating that the material exhibits a secondary phase transition. According to the Maxwell relationship, the magnetic entropy change |ΔS can be calculated from the isothermal magnetization curve M |. From the figure, we can see that under the external field of 5T |ΔS M |The maximum value is about 3.7 J / kg K, and appears near 297 K. Under an external field of 5 T, the operating temperature range can reach 90.5 K, and the refrigeration capacity (RCP) reaches 350 J / kg, showing good magnetic refrigeration capacity.
[0087] Table 1 Ce2Fe 17 Crystal structure parameters of base alloy, d Fe6c-6c , Formation Energy E form
[0088]
[0089]
[0090] Example 2 Ce 1.6 Nd 0.4 Fe 16.8 Si 0.2 Composition design and preparation
[0091] (1) The alloy composition design is the same as that in Example 1.
[0092] (2) Raw material preparation: According to the chemical formula Ce 1.6 Nd 0.4 Fe 16.8 Si 0.2 , weigh the raw materials Ce, RE, Fe, Si, among which the rare earth metal is added in excess of 5% to make up for the loss.
[0093] (3) Alloy smelting: Alloy ingots are smelted using vacuum induction melting technology. The weighed raw materials are placed in the crucible of a vacuum rapid solidification smelting furnace; vacuum is drawn to a vacuum degree of 7×10 -3 Pa; high-purity argon gas is introduced to make the pressure in the furnace 40kPa; electricity is supplied to melt the raw materials, and the liquid is automatically stirred by electromagnetic force for refining. The temperature of the alloy liquid is 1500℃ and kept warm for 4 minutes; then, the uniformly smelted alloy liquid is cast onto a rotating water-cooled copper plate to obtain an ingot with uniform composition.
[0094] (4) Alloy homogenization heat treatment: Place the above alloy ingot in a vacuum heat treatment furnace and evacuate to a vacuum degree better than 10 -2 Pa, and then high-purity argon gas was introduced and kept at 1050℃ for 5h. After the insulation, it was quickly quenched in water and cooled to room temperature.
[0095] The block was broken and measured, and X-ray diffraction proved that the main phase was Th2Zn 17 The 2:17R phase of the structure is a 2:17R phase, with only a very small amount of α-Fe phase. The phase transition temperature measured by PPMS is 273K. Under an external field of 5T, |ΔS M |The maximum value is about 3.5J / kg K, and appears near 273K. Under an external field of 5T, the operating temperature range can reach 92.5K, and the refrigeration capacity (RCP) reaches 340J / kg, showing good magnetic refrigeration capacity.
[0096] Example 3 Ce 1.6 Nd 0.4 Fe 16 Composition design and preparation of Si1
[0097] (1) The alloy composition design is the same as that in Example 1.
[0098] (2) Raw material preparation: According to the chemical formula Ce 1.6 Nd 0.4 Fe 16.5 Si 0.5 , weigh the raw materials Ce, RE, Fe, Si, among which the rare earth metal is added in excess of 5% to make up for the loss.
[0099] (3) Alloy smelting: Alloy ingots are smelted using vacuum induction melting technology. The weighed raw materials are placed in the crucible of a vacuum rapid solidification smelting furnace; vacuum is drawn to a vacuum degree of 7×10 -3 Pa; high-purity argon gas is introduced to make the pressure in the furnace 80kPa; electricity is supplied to melt the raw materials, and the liquid is automatically stirred by electromagnetic force for refining. The temperature of the alloy liquid is 1350℃ and kept warm for 10 minutes; then, the uniformly smelted alloy liquid is cast onto a rotating water-cooled copper plate to obtain an ingot with uniform composition.
[0100] (4) Alloy homogenization heat treatment: Place the above alloy ingot in a vacuum heat treatment furnace and evacuate to a vacuum degree better than 10 -2 Pa, and then high-purity argon gas was introduced and kept at 1200℃ for 2h. After the insulation, it was quickly quenched in water and cooled to room temperature.
[0101] The block was broken and measured, and XRD and SEM proved that the main phase was Th2Zn 17The 2:17R phase of the structure is a 2:17R phase, with only a very small amount of α-Fe phase. The phase transition temperature measured by PPMS is 298K. Under an external field of 5T, |ΔS M |The maximum value is about 3.5J / kg K, and appears near 298K. Under an external field of 5T, the operating temperature range can reach 100K, and the refrigeration capacity (RCP) reaches 380J / kg, showing good magnetic refrigeration capacity.
[0102] Example 4 Ce 1.33 Pr 0.67 Fe 16.67 Si 0.33 Composition design and preparation
[0103] (1) The alloy composition design is the same as that in Example 1.
[0104] (2) Raw material preparation: according to the composition Ce 1.33 Pr 0.67 Fe 16.67 Si 0.33 , weigh the raw materials Ce, RE, Fe, Si, among which the rare earth metal is added in excess of 5% to make up for the loss.
[0105] (3) Alloy smelting: Alloy ingots are smelted using vacuum induction melting technology. The weighed raw materials are placed in the crucible of a vacuum rapid solidification smelting furnace; vacuum is drawn to a vacuum degree of 7×10 -3 Pa; high-purity argon gas is introduced to make the pressure in the furnace 80kPa; electricity is supplied to melt the raw materials, and the liquid is automatically stirred by electromagnetic force for refining. The temperature of the alloy liquid is 1400℃ and kept warm for 8 minutes; then, the uniformly smelted alloy liquid is cast onto a rotating water-cooled copper plate to obtain an ingot with uniform composition.
[0106] (4) Alloy homogenization heat treatment: Place the above alloy ingot in a vacuum heat treatment furnace and evacuate to a vacuum degree better than 10 -2 Pa, and then high-purity argon gas was introduced and kept at 1150℃ for 3h. After the insulation, it was quickly quenched in water and cooled to room temperature.
[0107] The block was broken and measured, and XRD and SEM proved that the main phase was Th2Zn 17 The 2:17R phase of the structure is of type 2 and there is very little α-Fe phase. The SEM image is consistent with the X-ray diffraction results. The phase transition temperature measured by the comprehensive physical property measurement system (PPMS) is 280K. According to Maxwell calculation, Ce2Fe 17 Alloy under 5T external field |ΔS M |The maximum value is about 4.0 J / kg K, and the refrigeration capacity (RCP) reaches 366 J / kg, showing good magnetic refrigeration capacity.
[0108] Example 5 Ce 1.6 Pr 0.4 Fe 16.33 Si 0.67 Composition design and preparation
[0109] (1) The alloy composition design is the same as that in Example 1.
[0110] (2) Raw material preparation: according to the composition Ce 1.6 Pr 0.4 Fe 16.33 Si 0.67 , weigh the raw materials Ce, RE, Fe, Si, among which the rare earth metal is added in excess of 5% to make up for the loss.
[0111] (3) Alloy smelting: Alloy ingots are smelted using vacuum induction melting technology. The weighed raw materials are placed in the crucible of a vacuum rapid solidification smelting furnace; vacuum is drawn to a vacuum degree of 7×10 -3 Pa; high-purity argon gas is introduced to make the pressure in the furnace 80kPa; electricity is supplied to melt the raw materials, and the liquid is automatically stirred by electromagnetic force for refining. The temperature of the alloy liquid is 1400℃ and kept warm for 8 minutes; then, the uniformly smelted alloy liquid is cast onto a rotating water-cooled copper plate to obtain an ingot with uniform composition.
[0112] (4) Alloy homogenization heat treatment: Place the above alloy ingot in a vacuum heat treatment furnace and evacuate to a vacuum degree better than 10 -2 Pa, and then high-purity argon gas was introduced and kept at 1100℃ for 3h. After the insulation, it was quickly quenched in water and cooled to room temperature.
[0113] The block was broken and measured, and XRD and SEM proved that the main phase was Th2Zn 17 The 2:17R phase of the structure is of type 2 and there is very little α-Fe phase. The SEM image is consistent with the X-ray diffraction results. The phase transition temperature measured by the comprehensive physical property measurement system (PPMS) is 289K. According to Maxwell calculation, Ce2Fe 17 Alloy under 5T external field |ΔS M |The maximum value is about 3.6 J / kg K, and the refrigeration capacity (RCP) reaches 351 J / kg, showing good magnetic refrigeration capacity.
[0114] It can be seen from the comparative examples that the phase transition temperature of the material prepared in comparative example 1 is far below room temperature, and the phase transition temperature of the material prepared in comparative example 2 is near zero degrees, but the α-Fe phase content is high and the heat treatment time is long. It can be seen from the embodiments that the phase transition temperature of the materials prepared in the embodiments is near room temperature, the α-Fe phase content is low, and the heat treatment time is short. From the perspective of magnetic entropy change and magnetic refrigeration capacity, the embodiments are greater than comparative example 1 and equivalent to comparative example 2, indicating that the composite addition of rare earth elements and Si helps to obtain RE-Fe room temperature magnetic refrigeration materials with uniform structure and excellent performance.
Claims
1. A design method for RE-Fe based room temperature magnetic refrigeration material, characterized in that: The chemical formula of the designed room temperature magnetic refrigeration material is: Ce 2-x RE x Fe 17-y Si y , wherein RE is selected from Pr, Nd, and 0.1≤x<0.5, 0.2<y≤1; The design method adopts the first principle calculation method based on density functional theory, the calculation is performed using VASP software package, and the projected enhanced wave method and GGA-PBE exchange correlation potential are used for calculation; the steps are as follows: ① Selection of basic parameters for calculation Select lattice constant a =8.496Å, c =12.415Å Ce2Fe 17 The unit cell is used as the initial structure. The unit cell contains 57 atoms, of which Ce occupies the 6c position, and Fe occupies the 6c, 9d, 18f and 18h positions respectively. 2-x RE x Fe 17-y M y The unit cell parameters and atomic occupancy of the model are completely relaxed, and the convergence criteria for electronic self-consistency and ion relaxation are set to 10 -7 eV and 0.005 eV / Å, the cutoff energy is 600 eV, and the K-point grid is 5 × 5 × 3; in addition, the "Hubbard U" method is used to treat the 4f orbitals of rare earth atoms, and the U value of Ce is taken as 4 eV; Wherein RE is selected from one of Pr, Nd, Sm, La, Dy, Gd, M is selected from one of Si, Al, Ga, Ge, Sn, P, Mg, Cr, Ti, and V; ② Atoms in Ce2Fe 17 Occupancy calculation in unit cells; Substituting M atoms for Ce2Fe 17 The Fe at the 6c, 9d, 18f and 18h crystal positions in the unit cell are calculated according to the calculation parameters in ① to calculate the Ce2Fe containing M. 17 The formation energy of the unit cell E form , determine that M atoms are in Ce2Fe 17 Atomic occupancy in a unit cell; ③ Alloy composition design According to the calculation results of ②, Si atoms are selected to occupy the position, and RE atoms are substituted for the 6c crystal position of Ce. According to the calculation parameters in ①, Ce is calculated and obtained. 2-x RE x Fe 17-y M y The cell parameters a and c of the alloy were obtained, and the c / a value and the atomic distance between Fe atoms at the 6c crystal position were obtained to quantitatively determine the influence of alloy composition on the Curie temperature. 2-x RE x Fe 17-y M y The formation energy of the alloy is calculated to be: when RE is selected from Pr or Nd; M is Si, and 0.1≤x<0.5, 0.2<y≤1, the formation energy of the alloy is the lowest, so the chemical formula of the magnetic refrigeration material is designed: Ce 2-x RE x Fe 17-y Si y , wherein RE is selected from Pr or Nd, and 0.1≤x<0.5, 0.2<y≤1.
2. A method for preparing a RE-Fe-based room temperature magnetic refrigeration material designed by the design method according to claim 1, characterized in that: The steps include: According to the designed proportion, the raw materials Ce source, RE source, Fe source and Si source are weighed, and then the Ce source, RE source, Fe source and Si source are smelted under a protective atmosphere, the uniformly smelted alloy liquid is cast to obtain an alloy ingot, the alloy ingot is heat treated under a protective atmosphere, and cooled to obtain the alloy.
3. The method for preparing a RE-Fe based room temperature magnetic refrigeration material according to claim 2, characterized in that: The raw materials are placed in the crucible of the vacuum rapid solidification melting furnace; vacuum is drawn to make the vacuum degree in the furnace ≤5×10 -2 Pa; introduce argon gas to make the pressure in the furnace 40-80kPa; send electricity to melt the raw materials, and use electromagnetic force to automatically stir the liquid for refining.
4. The method for preparing a RE-Fe based room temperature magnetic refrigeration material according to claim 2, characterized in that: The smelting temperature is 1350-1500° C., and the smelting time is 4-10 minutes.
5. The method for preparing a RE-Fe based room temperature magnetic refrigeration material according to claim 2, characterized in that: The uniformly molten alloy liquid is poured onto a rotating water-cooled copper plate to obtain an alloy ingot.
6. The method for preparing a RE-Fe based room temperature magnetic refrigeration material according to claim 2, characterized in that: The heat treatment temperature is 1050-1200° C., and the heat treatment time is 2-5 hours.
7. The method for preparing a RE-Fe based room temperature magnetic refrigeration material according to claim 2, characterized in that: After the heat treatment is completed, it is quickly quenched in water and cooled to room temperature.
8. Application of a RE-Fe based room temperature magnetic refrigeration material designed by the design method according to claim 1, characterized in that: The RE-Fe-based room temperature magnetic refrigeration material is applied to the field of room temperature refrigeration or the field of magnetic thermal ice melting.
Citation Information
Patent Citations
Mixed rare-earth-based refrigerating material as well as preparation method and application thereof
CN110551941A
Rare earth iron-base room-temp mangnetic refrigerant material and preparation method thereof
CN1598977A
High-thermal-conductivity room temperature magnetic refrigeration situ composite and preparation method and application thereof
CN105986177A
Lanthanum-free mixed rare earth-based room-temperature magnetic refrigeration material and preparation and application thereof
CN111172457A